YouTube Keyword Search Engine Using Speech Recognition - Aymen Shakat; Khaldun Ibraheem Arif; Sami Hasan; Yaser Dawood; Mohammed A. Mohammed (Iraqi Journal of Science, 2021)
Visual media is a better way to deliver the information than the old way of "reading". For that reason with the wide propagation of multimedia websites, there are large video library’s archives, which came to be a main resource for humans. This research puts its eyes on the existing development in applying classical phrase search methods to a linked vocal transcript and after that it retrieves the video, this an easier way to search any visual media. This system has been implemented using JSP and Java language for searching the speech in the videos